Praktek Menjaga Hafalan Al- Qur’an Santri Pondok Pesantren Tahfidh Yanbu’ul Qur’an Menawan Kudus - Surya Wahyu Hanggara (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
Memorizing the Qur'an is a tradition that has long been carried out by the Prophet, in which the Prophet Muhammad received revelations in the form of the Qur'an by memorizing, and applying the contents of the Qur'an in everyday life, and calling for Islamic teachings contained in the Qur'an to his people so that the Qur'an is maintained to this day. Meanwhile, hadith is an important part for society because it reveals various traditions at the time of the Prophet. At the Tahfidh Yanbu'ul Qur'an Menawan Kudus Islamic Boarding School, in practice carrying out the memorizing of the Qur'an. By using the basis of one of the hadiths of the Prophet which states that Guard the Qur'an. For the sake of the Essence who controlled the soul of Muhammad, the Qur'an is actually faster than a camel in its rope. The Qur'an is the most important word and is full of laws, reading it is a worship that melts the heart, makes the soul solemn and provides countless other benefits. Therefore, the Prophet SAW ordered to always take care of it so as not to forget. The practice of keeping students memorized the Qur'an at the Tahfiz Yanbu'ul Qur'an Menawan Islamic Boarding School includes: getting used to reading the Qur'an, having a murojaah program, playing a murottal Al-Qur'an, and memorizing the Qur'an. 'an, there is a random activity.